2011
DOI: 10.1016/j.paid.2010.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Understanding cooperation in the Prisoner’s Dilemma game

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. In the standard one-shot Prisoner's Dilemma game, participants often choose to cooperate, when the optimal strategy is to defect. This puzzling finding has attracted considerable interest both in terms of possible computational frameworks for modeling human judgment, but also regarding the more general debate of human altruism. In this research, we ask how much of human behavior in this task c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
61
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(64 citation statements)
references
References 15 publications
1
61
0
2
Order By: Relevance
“…After few computations, calling V (t) = e i U t and V k,l (t) its (k, l)-matrix element, we deduce that 14) and…”
Section: Ii4 the Effect Of Exchange Interactionmentioning
confidence: 99%
“…After few computations, calling V (t) = e i U t and V k,l (t) its (k, l)-matrix element, we deduce that 14) and…”
Section: Ii4 the Effect Of Exchange Interactionmentioning
confidence: 99%
“…Scheres and Sanfey (2006) found associations of BAS-RR and BAS-D with lower offers in the Dictator Game (which is similar to the UG except that the respondent does not have an opportunity to reject the offer) but not in the UG. Pothos et al (2011) showed that participants high in BAS-RR were more likely to defect in the one-shot prisoner's dilemma game. In all cases, participants high in reward reactivity, made a decision to defect while having full control of the situation and no dependency on the decision of other people.…”
Section: Individual Differences In Social Dilemmamentioning
confidence: 99%
“…only one round of the game is played) [23] and more likely to cooperate unconditionally in a commons dilemma when the resource was severely threatened [24]. They were also more likely to cooperate in a one-shot PD, but only when the payoff structure was such that cooperation, rather than defection, was the optimal strategy [25], and in the first round of an iterated PD (IPD; i.e. the game is played for repeated rounds, as opposed to a one-shot game) [26].…”
Section: Introductionmentioning
confidence: 99%
“…Performancebased monetary incentives were implemented by Volk et al [23], Kurzban & Houser [27] and Skatova & Ferguson [33] in the PGG and by Lönnqvist et al [36] and Kagel & McGee [26] in the PD. However, they were not used by Hilbig et al [28] in one-shot PGG without and with punishment nor by Pothos et al [25], Hirsh & Peterson [29] or Zettler et al [39] in the PD. Boone et al [32] and Koole et al [24] motivated players with prizes awarded to a few participants with the highest payoffs in PD and commons resource games, respectively (Koole et al [24] used a lottery, with odds determined by points accumulated in the commons game), but players could not attach an exact monetary value to the decisions with which they were faced.…”
Section: Introductionmentioning
confidence: 99%